Analisis Indeks Kualitas Tanah dan Hubungannya dengan Prdoduktivitas Tanaman Buah - Baskoro, Dwi Putro Tejo; Purwakusuma, Wahyu; Hidayat, Yayat; Malahayati, Sri; Wahyu Purwakusuma (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2025)
Soil quality is a determining factor for crop production. Therefore, proper assessment of soil quality—by integrating various soil characteristics into a Soil Quality Index (SQI)—is essential to reflect overall soil productivity. This study aimed to determine the SQI and its relationship to fruit crop productivity across seven locations with varying soil characteristics. The research was conducted at SMK PP Saree and SMKN Nisam in Aceh Province; SMKN Gelumbang and SMKN Banyuasin 3 in South Sumatra Province; SMKN Metro and SMKN Gedong Tataan in Lampung Province; and SMKN Kelapa in Bangka Belitung Province. The SQI analysis used eight key soil parameters considered critical for determining and managing crop growth and productivity, namely: effective soil depth, texture, bulk density, pH, organic matter content, cation exchange capacity (CEC), and base saturation. Each parameter was scored on a scale from 0 to 5. The results showed that the Soil Quality Index can effectively assess soil quality using these eight key parameters as a dataset. The studied soils were categorized as having medium to very good quality, with low organic carbon and low CEC identified as the most common limiting factors. Furthermore, the SQI demonstrated a strong positive correlation with fruit crop performance, with a correlation coefficient (r) of 0.832.